Distribución, diversidad y conservación de los mamíferos de importancia cinegética en México. - Uribe, Jorge; T. Arita, Héctor (Instituto de Ecología, A.C., 1998)
Littie is known about the large-scale patterns of distribution of Mexican game mammals. Here we analyze the distribution, the diversity patterns, and the conservation status of the Mexican fauna of game mammals. For the análisis, we considered three different hunting activities: subsistence, commercial and sport hunting (bats, insular, and exotic species were not considered in the analyses). We included in our definition of "game species" all mammals that are hunted or trapped during the three mentioned activities. At least 104 mammalian species are hunted in México, representing 22% of the whole terrestrial non-volant fauna of Mexican mammals. The hunting zona 3 in the State of Sonora has the highest number of game mammals, including 49 species, whereas the hunting zone with the lowest richness corresponds with the hunting zone 4 in Baja California Sur, with 15 species. For compartng spcies richness among States we used regression techniques. We found that ten Mexican States have a higher number of game species than expected for their area. The endemic game mammals are poorly representad in México and there is a poor correspondence between the whole endemic mammal fauna and the endemic game fauna. Some geographic distributional patterns that are implicit in the official hunting regulations do not correspond with the information that we gathered. Our results suggest that the Mexican regulations regarding subsistencé and commercial hunting in México should be revisad.